Assessment of Health-Related Quality of Life and Associated Factors among Type 2 Diabetes Mellitus Patients Attending a Tertiary Care Hospital - Nyamagoud, Sanatkumar Bharamu; Swamy, Agadi Hiremath Viswanatha; Kangrali, Bharati (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Type 2 diabetes mellitus is a chronic disease that can affect the quality of life of individuals. Health-Related Quality of Life (HRQOL) is an important outcome measure in assessing the impact of diabetes on individuals' lives. This study aimed to assess the HRQOL of individuals with type 2 diabetes in India using the SF-36 questionnaire, identify factors associated with HRQOL, and evaluate the overall QOL of this population. Materials and Methods: In this study, 300 individuals with type 2 diabetes mellitus were recruited from tertiary care hospitals in India. The Health-Related Quality of Life (HRQOL) assessment was conducted using the SF-36 questionnaire, which evaluates eight domains of QOL. A structured questionnaire was used to collect demographic and clinical data. Multiple linear regression was employed to identify factors that are associated with HRQOL. Results: The mean age of participants was 56.5 years, and 53% were male. The mean scores for all eight domains of the SF-36 questionnaire were lower in individuals with type 2 diabetes compared to the general population in India. The most affected were physical functioning, role-physical, bodily pain, and vitality domains. Multiple linear regression analysis revealed that age, gender, education, duration of diabetes, and comorbidities were significantly associated with HRQOL. Conclusion: Individuals with type 2 diabetes mellitus in India have lower HRQOL than the general population. The physical health domains of the SF-36 questionnaire were the most affected. Age, gender, education, duration of diabetes, and comorbidities were identified as important factors associated with HRQOL. This study highlights the need for interventions to improve the QOL of individuals with type 2 diabetes mellitus in India.
Keywords: Diabetes Mellitus; Quality of life; Type 2 DM; Factors; Clinical Pharmacy; Clinical; Pharmacist